PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI PADA MATA PELAJARAN IPS DI SMP PANCA SETYA 1 SINTANG - Mariana, Nina; Relita, Dessy Triana; Marganingsih, Anna (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
Success in the learning process is very dependent on the availability of learning media that supports the achievement of learning objectives. Well-designed learning media has the potential to have a positive impact in developing students' potential. One of the effective tools in the learning process is the Monopoly game media. This research uses a Research and Development approach with the ADDIE model, which includes Analysis, Design, Development, Implementation and Evaluation. The research sample consisted of 28 students from class VIII C. Data analysis involved evaluation by media experts and product users, using percentage intervals to assess the suitability of the product. The results of the development research show that the Monopoly learning media is suitable for use, with a validation rate of media experts of 87.6%, material experts of 86.3%, and learning practitioners of 81.33%. Small group trials and field trials showed a high level of feasibility, with percentages of 94.9% and 81.33% for student learning completion. Based on the results of this assessment, it can be concluded that the Monopoly learning media is very suitable for use in learning social studies subjects.